2016
DOI: 10.1053/j.ajkd.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Kidney Injury Among Nicaraguan Sugarcane Workers

Abstract: Background In Central America, an epidemic of chronic kidney disease of unknown etiology disproportionately affects young, male agricultural workers. Study Design Longitudinal cohort study. Setting & Participants 284 sugarcane workers in seven jobs were recruited from one company in northwestern Nicaragua. Blood and urine samples were collected before and near the end of the six-month harvest season. Predictors Job category (cane cutter, seeder, seed cutter, agrichemical applicator, irrigator, driver, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 54 publications
7
92
1
2
Order By: Relevance
“…In a large-scale retrospective analysis including 13,201 patients without renal disease, elevated sOsmo independently predicted the development of CKD over a follow-up period of 5 years [8]. In addition, sOsmo has been linked to the development of CKD in the absence of classic risk factors (e.g., DM and hypertension) [9, 10]. In contrast to these earlier reports, we demonstrate similar associations with respect to short-term renal injury after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…In a large-scale retrospective analysis including 13,201 patients without renal disease, elevated sOsmo independently predicted the development of CKD over a follow-up period of 5 years [8]. In addition, sOsmo has been linked to the development of CKD in the absence of classic risk factors (e.g., DM and hypertension) [9, 10]. In contrast to these earlier reports, we demonstrate similar associations with respect to short-term renal injury after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The theory that this was a result of direct exposure to pesticides in the fields, however, is weakened by the presence of the disease in occupations not involving farming, by reports that there is a greater risk for renal injury in the sugarcane fields among the cane cutters as opposed to the pesticide applicators, and because the frequency of the disease is lower in sugarcane cutters working at higher altitudes where it is significantly cooler than at lower altitudes, despite similar agrochemical exposure (32,36,47). Nevertheless, it remains possible that toxins, for example, could be concentrating in well water that could affect the populations as a whole.…”
Section: Mesoamerican Nephropathymentioning
confidence: 99%
“…Several studies suggest a causal association between MeN and chronic heat stress and dehydration (8)(9)(10)(11)(12)(13) and experimental data have shown that repeated dehydration can induce CKD in mice (14,15). Heat exposure, strenuous exercise and dehydration pose a significant challenge to the cardiovascular system, and the transport of oxygen to exercising muscles and vital organs, such as the kidney (16).…”
Section: Wegman Et Almentioning
confidence: 99%